Participatory action research to address aging out of LGBTQ-supportive youth programs in Chicago. Issue 2 (3rd April 2022) - Felner, Jennifer K.; Dyette, Omar; Dudley, Terry; Farr, Amanda; Horn, Stacey
Abstract: LGBTQ-supportive youth programs provide access to critical resources and social support in identity-affirming environments. In Chicago, Illinois, an informal network of LGTBQ-supportive youth programs in the city's white, middle-class, gay enclave, Boystown, draws predominately low-income youth of color from across the city who seek emergency shelter, housing, educational assistance, mental health counseling, space to build community with peers, and more. Upon their 25th birthday, however, these young people are abruptly "aged out" of LGBTQ-supportive youth programs, often with little preparation and few safety nets to support their transition into adulthood. Aging out has been examined in other service contexts (e.g., foster care); rarely, however, has it been examined among youth accessing LGBTQ-supportive programs. This article draws on applied thematic analysis of qualitative data from focus groups with young people ages 20-29 (n = 26) and interviews with service providers (n = 10) collected via youth participatory action research to examine how young people experience accessing and aging out of LGBTQ-supportive programs in Chicago. Findings highlight a lack of scaffolding for youth as they age out and extremely limited safe and affirming resources for LGBTQ adults. Recommendations are provided to better support young people in their transition out of LGBTQ-supportive youth services and into adulthood.